The Design Approach of Ethereum-based Student Achievement Record System on Private Blockchain Network - Yan Watequlis Syaifudin (CV. Creative Tugu Pena, 2024)
Blockchain transformative technology that enables secure, decentralized, and immutable transaction recording through a network of cryptographic blocks, enhancing transparency and trust without the need for a central authority or intermediaries. The Ethereum platform builds upon this foundation by facilitating the development of decentralized applications (dApps) and smart contracts, which automate processes and improve operational efficiency. In higher education, the Student Activity Credit Unit (SACU) system exemplifies the application of blockchain by managing both academic and non-academic achievements, thus promoting a holistic approach to student development and enhancing essential soft skills like leadership and teamwork. By leveraging a decentralized system built on Hyperledger Besu, the SACU ensures that student records are secure, transparent, and scalable, while providing real-time monitoring and verification of achievements. This paper evaluates the decentralized student’s achevements record model, demonstrating its improvements in transparency, security, and efficiency over existing systems, ultimately preparing graduates for professional success and fostering trust in the recognition of their qualifications.